2019
DOI: 10.1111/echo.14275
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of global and territorial longitudinal strain imaging in detecting significant coronary artery disease in patients with myocardial infarction without persistent ST‐segment elevation

Abstract: Introduction Two‐dimensional (2D) speckle‐tracking echocardiographic (STE) imaging is frequently performed in the assessment of cardiovascular diseases. We aim to investigate the role of the global and territorial longitudinal strain (GLS and TLS) values assessed via 2D STE imaging to detect significant coronary artery disease (CAD) in non‐ST‐segment elevation myocardial infarction (NSTEMI) patients without wall‐motion abnormalities. Methods This study enrolled 150 patients with the diagnosis of NSTEMI. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
5
6
0
1
Order By: Relevance
“…We also found that MWs in LAD segments had higher diagnostic value than MWs in LCX or RCA territories. In consistency with previous studies, the accuracy of 2D-STE was greater in the LAD territory, compared with other territories [22][23][24]. In our study, most MWs in LAD and RCA segments can predict relevant stenoses.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that MWs in LAD segments had higher diagnostic value than MWs in LCX or RCA territories. In consistency with previous studies, the accuracy of 2D-STE was greater in the LAD territory, compared with other territories [22][23][24]. In our study, most MWs in LAD and RCA segments can predict relevant stenoses.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, as the high sensitivity troponin values increased, the GLS decreased significantly. 10 Thus, quantification of strain abnormalities can have prognostic value in acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…(9)Early major OM was considered an intermedio-lateral branch and the antero-lateral overlap territory was assigned to it. (10) PDA and PLB lesions were assigned to RCA or LCX depending on the dominance. In a co-dominant system, depending on which vessel had the lesion, the analysis was done.…”
Section: Angiographymentioning
confidence: 99%
“…Após um período de 2 semanas, pode ocorrer melhora acentuada da função ventricular. 301 Com as novas tecnologias desenvolvidas nos aparelhos de ecocardiografia, como speckle-tracking 2D, tem sido possível, por meio da análise do strain global longitudinal (SGL) das paredes do VE, diagnosticar precocemente alterações isquêmicas em pacientes com alteração de troponina, porém sem alteração do ECG ou ecocardiograma de repouso (25% a 75% dos paciente com SCA têm ecocardiograma normal). 302 O SGL (quando < 16,5%) pode complementar algoritmos diagnósticos existentes e agir como marcador adjunto precoce de isquemia.…”
Section: Teste Ergométricounclassified